No ghost under my bed - Genechten, Guido van (Clavis, 2010)
When a little penguin named Jake becomes afraid of strange noises in his room at night, he calls his father to check out the situation, and when everything from the curtain to the wardrobe and toy box has been checked, Jake feels comforted that all of the ghosts are gone and prepares to sleep.